Клінічні випадки гіпертрофічної кардіоміопатії у котів - Тішкіна, Наталія Миколаївна; Tishkina, Natalіia; Tishkina, Natalya; Tishkina, N.; Tishkina, N. N.; Tishkina, N. M.; Сапронова, Валентина Олексіївна; Sapronova, V.; Sapronova, Valentina; Sapronova, V. A.; Sapronova, V. O.; Римський, Владислав Вікторович; et al. (Полтавський ДАУ, 2022)
У роботі проаналізовано клінічні випадки захворюваності котів на гіпертрофічну кардіоміопатію. Дослідження проведено в період 2021 та початку 2022 років в умовах ТОВ «Ветеринарний простір Діскавері» м. Дніпра. Об’єктами клінічного і лабораторного дослідження послужили 17 свійських котів різних вікових груп, статі та порід, які під час комплексного дослідження мали яскраво виражену клініку. Захворювання реєстрували серед кастрованих тварин британської, шотландської, персидської породи, породи сфінкс та мейн-кун. Віковий діапазон складав від 1,5 до 13 років, середній вік тварин 6, 7 років. Більшість котів явних клінічних ознак не проявляли. Візуально у хворих тварин з гіпертрофічною кардіоміопатією спостерігали клінічні ознаки, що були характерними для серцевої недостатності – в’ялість, апатичність, швидке стомлення, задишку, раптову непритомність Для постановки діагнозу проводили збір анамнезу, клінічне і лабораторне дослідження. Спеціальне обстеження включало рентгенографію грудної клітки, електрокардіографію та ультразвукову діагностику серця. Для більшості котів з клінічними ознаками, спричиненими гіпертрофічною кардіоміопатією, довгостроковий прогноз від обережного до несприятливого, залежно від клінічного стану тварин та перебігу хвороби та, незважаючи на лікування. Лікування тварин було направлено на контроль частоти серцевих скорочень, зменшення набряків легень та застою при застійній серцевій недостатності, розчиненню наявних тромбів та запобіганню їх появі. Під час лікування чотири тварини (25,5 %) загинули та трьох (17,7 %) евтаназували на прохання власників. Після проведеного лікування загальний стан покращився у шести тварин (35,3 %), ще четверо (25,5 %) померли протягом місяця після закінчення лікування. The clinical cases of cats with hypertrophic cardiomyopathy were analyzed. The study was conducted in 2021 and early 2022 in the conditions of LLC "Veterinary Space Discovery", Dnipro. The objects of clinical and laboratory research were 17 domestic cats of different age groups, sexes and breeds, which during the complex study had a pronounced clinic. For most animals, the cause of cardiomyopathies is unknown, a genetic predisposition has been found in cats of the Maine Coon, Regdol and Sphinx breeds. Diseases have been reported among castrated animals of British, Scottish, Persian, Sphinx and Maine Coon breeds. The age range was from 1.5 to 13 years, the average age of animals was 6.7 years. Most cats did not show obvious clinical signs. Visually, in sick animals with hypertrophic cardiomyopathy, clinical signs characteristic of heart failure were observed – lethargy, apathy, rapid fatigue, shortness of breath, sudden fainting. Special examinations included chest radiography, electrocardiography, and ultrasound of the heart. Radiography revealed pulmonary edema and serous effusion in the thoracic cavity in 18 % of animals. Electrocardiographic analysis included rhythm diagnosis and specific electrocardiographic measurements, which revealed arrhythmias in three animals (18 %). Cardiomegaly and concentric or asymmetric left ventricular hypertrophy have been reported in echocardiography in affected cats. Concentric hypertrophy was characterized by thickening of the wall and reduction of the left ventricular cavity, with gradual expansion of the left atrium. Also, 53 % of animals showed systolic murmur and 24 % gallop murmur, which is an additional indicator of hypertrophic cardiomyopathy. For most cats with clinical signs of hypertrophic cardiomyopathy, the long-term prognosis is from cautious to adverse, depending on the clinical condition of the animals and the course of the disease and despite treatment. Treatment of animals was aimed at controlling heart rate, reducing pulmonary edema and stagnation in congestive heart failure, dissolving existing blood clots and preventing their occurrence. During treatment, four animals (25.5 %) died and three (17.7 %) were euthanized at the request of the owners. After treatment, the general condition improved in six animals (35.3 %), four more (25.5 %) died within a month after treatment.
Clinical cases of hypertrophic cardiomyopathy in cats
Тішкіна Наталія Миколаївна http://orcid.org/0000-0003-2662-5327 Сапронова Валентина Олексіївна https://orcid.org/0000-0002-0063-5773 Римський Владислав Вікторович https://orcid.org/0000-0001-5394-7036
Keywords: лікування; treatment; коти; cats; хвороба серця; heart disease; ехокардіографія; echocardiography; серцева недостатність; heart failure; набряк легень; pulmonary edema